Assessment of the Knowledge, Attitude, and Practice of Root Canal Treatment Among Pediatric Dentists - Karkar, Dr. Monal; Kumar Swarnkar, Dr. Sandeep; Anannya Dutta, Dr. Rajashree; Pratim Saikia, Dr. Priyam; Verma Baghel, Dr. Apoorvi; Tiwari, Dr. Manishi (Journal of Neonatal Surgery, 2025)
Background: Root canal treatment (RCT) is vital in pediatric dental care to preserve primary and young permanent teeth. Despite its significance, variations in pediatric dentists' knowledge, attitude, and practice (KAP) can influence treatment outcomes. This study aimed to assess the current status of KAP regarding RCT among pediatric dental practitioners. Aim: To evaluate the KAP of root canal treatment among pediatric dentists and identify factors influencing their clinical decision-making. Methods: A cross-sectional, questionnaire-based study was conducted among 216 pediatric dentists. A structured and validated online questionnaire was distributed, covering demographic data and specific questions related to RCT KAP. Descriptive statistics, Chi-square tests, t-tests, ANOVA, and Spearman’s correlation were used for data analysis. A p-value < 0.05 was considered statistically significant. Results: Most participants (52.3%) demonstrated moderate knowledge of RCT, while 30.1% showed good knowledge. Most respondents acknowledged the importance of RCT but cited behavioral challenges and anatomical complexity as obstacles. Clinical practice patterns revealed acceptable use of resorbable materials and apex locators, though only 47.7% attended regular continuing education programs. Statistically significant correlations were found between knowledge and both attitude (r = 0.42, p< 0.001) and practice (r = 0.39, p< 0.01), indicating that improved knowledge positively influenced professional behavior. Conclusion: While pediatric dentists generally maintain a positive attitude toward RCT, gaps in knowledge and practice remain. Continuous education and structured training programs are essential to enhance clinical competency and ensure standardized care in pediatric endodontics.